2016
DOI: 10.1016/j.cmpb.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A predictive mechanical model for evaluating vertebral fracture probability in lumbar spine under different osteoporotic drug therapies

Abstract: Osteoporotic vertebral fractures represent a major cause of disability, loss of quality of life and even mortality among the elderly population. Decisions on drug therapy are based on the assessment of risk factors for fracture from bone mineral density (BMD) measurements. A previously developed model, based on the Damage and Fracture Mechanics, was applied for the evaluation of the mechanical magnitudes involved in the fracture process from clinical BMD measurements. BMD evolution in untreated patients and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…At present, osteoporotic fracture is considered to be an important public health problem that not only increases morbidity and mortality in the elderly, but also incurs important economic costs. In addition, osteoporotic lumbar fracture often causes spinal cord injury, which is the main cause of disability, reduced quality of life, and even death in the elderly [ 1 ]. Thoracolumbar vertebra refers to T 11 –L 2 , which is a special segment of the spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, osteoporotic fracture is considered to be an important public health problem that not only increases morbidity and mortality in the elderly, but also incurs important economic costs. In addition, osteoporotic lumbar fracture often causes spinal cord injury, which is the main cause of disability, reduced quality of life, and even death in the elderly [ 1 ]. Thoracolumbar vertebra refers to T 11 –L 2 , which is a special segment of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is one of the common basic diseases in the elderly with calcium loss in the body and bone mass reduction which is more prone to cause fracture and occur in the thoracolumbar vertebrae [ 1 , 2 ]. Osteoporosis is a systemic skeletal disease, the occurrence and development of which is the result of the comprehensive action of many systems, such as nerve, endocrine, immunity, reproduction, musculoskeletal, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we decided to study the lumbar spine segment, as recently evaluated in a predictive mechanical model for evaluating vertebral fracture probability in lumbar spine under different osteoporotic drug therapies. 32 In future studies, we are planning to study localization of metastasis to the thoracic spine. Finally, our study did not consider metastases on multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, osteoporosis is a major public health issue, which slowly evolves as an asymptomatic condition, with increasing probabilities of developing fragility fractures (MCCLUNG, 2005;LÓPEZ et al, 2016). Studies have shown that a previous spine fracture increases the risk of future hip fracture, which in turn is associated with increased morbidity and mortality in elderly people (TELLACHE et al, 2009;HAMMERNIK et al, 2015).…”
Section: Hypothesismentioning
confidence: 99%
“…As one of the most common fracture occurs in the vertebra (MEHTA; SEBRO, 2020;LÓPEZ et al, 2016), predicting occurrence of this injury is crucial for prevention and early treatment. Bone mineral density (BMD) is one of the reference indicators employed to diagnose osteoporosis, and is associated to an increased risk of fractures, including lumbar and hip fractures (MCCLUNG, 2005;MEHTA;SEBRO, 2020;WU et al, 2020).…”
Section: Hypothesismentioning
confidence: 99%